2018
DOI: 10.4244/eij-d-17-00859
|View full text |Cite
|
Sign up to set email alerts
|

Less invasive fractional flow reserve measurement from 3-dimensional quantitative coronary angiography and classic fluid dynamic equations

Abstract: The aim of this study was to develop a simplified model of FFR calculation (FFR sim ) derived from three-dimensional (3D) coronary angiographic data and classic fluid dynamic equations without using finite element analysis.Methods and results: Intracoronary pressure measurements were performed by pressure wire sensors.The lumens of the interrogated vessel segments were reconstructed in 3D. The coronary artery volumetric flow was calculated based on the velocity of the contrast material. Pressure gradients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
0
14
0
1
Order By: Relevance
“…FFR sim is an angiography-derived FFR methodology that is based on 3D-QCA and classic fluid dynamics equations without using finite element analysis [21].…”
Section: Simplified Model Of Ffr Calculation (Ffr Sim )mentioning
confidence: 99%
See 1 more Smart Citation
“…FFR sim is an angiography-derived FFR methodology that is based on 3D-QCA and classic fluid dynamics equations without using finite element analysis [21].…”
Section: Simplified Model Of Ffr Calculation (Ffr Sim )mentioning
confidence: 99%
“…Finally, this allows calculation of FFR sim which is defined as Pd/Pa across as stenosis. Tar et al studied 68 vessels with single-vessel stenosis where FFR sim shows strong correlation with invasive FFR (r � 0.86, p < 0.0001) [21]. e sensitivity and AUC of FFR sim to detect haemodynamically significant lesions (FFR < 0.80) were 0.90 and 0.96, respectively.…”
Section: Simplified Model Of Ffr Calculation (Ffr Sim )mentioning
confidence: 99%
“…Mivel ez a legkevésbé invazív és legolcsóbb módszer, így amennyiben további tanulmányok helyen lesz javasolható a képalapú (image based FFR) -számíthatjuk ki bizonyos pontossággal az éren kialakuló nyomásesést. Az eddigi eredmények szerint ezek a kevésbé invazív módszeren alapuló képalapú FFR-értékek jól közelítik az invazív módszerrel mért FFR-t (28)(29)(30)…”
Section: A Nonhyperaemiás Nyomásparaméterek Klinikai Alkalmazásaunclassified
“…In our previous study, on a less invasive FFR measurement, we proposed a new simplified model developed for the estimation of FFR [2]. It was found that this method was suitable for characterizing every single intermediate stenosis with an especially good positive predictive value; furthermore, the calculations only require a simple MS Excel sheet for the input of the hyperemic flow velocity values and the data of the three-dimensional coronary reconstruction.…”
mentioning
confidence: 99%
“…The purpose of this present study was to perform a retrospective analysis on the cases of the previous study [2] to assess the accuracy of FFR calculations using the fixed hyperemic contrast flow, the resting frame count, and the hyperemic frame count data.…”
mentioning
confidence: 99%